Further notes on Munchausen's syndrome: a case report of a change from acute abdominal to neurological type - Barnett, Winfried; Vieregge, Peter; Jantschek, Guenter (Journal of neurology, 1990)
A rare case of Munchausen's syndrome beginning in early childhood is described. The diagnosis of Munchausen's syndrome was made at the age of 29 years, after the symptoms had changed from acute abdominal to neurological complaints, with feigned loss of consciousness, first ascribed to an encephalitis. Insight into the psychopathology of this patient is given by his biography, by assessment of a psychotherapist, who had treated him some years before, and by his observed profile in some psychological tests.
Gesehen am 08.12.2020